1996
DOI: 10.1109/20.538880
|View full text |Cite
|
Sign up to set email alerts
|

Hot pressing Nd-Fe-B HDDR powders

Abstract: Details of the important parameters for hot pressing isotropic Nd16Fe76BS HDDR powders are presented. Optimum magnetic properties may he achieved over broad ranges of green compaction pressure .and hot pressing temperature, time and pressure. Isotropic HDDR powders with lower Ndcontents (i.e. Nd14Fe79B7 and N d 1 3 F e 8 0 . 5 B 6 . 5 ) may also be hot pressed to full density to p5oduce magnets with energy products -1 0 0 k J / m and some advantages of hot pressing the lower Ndcontent compositions are stated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
3
1
Order By: Relevance
“…Such a phenomenon has not been reported in previous studies using the conventional hot-press [8,[14][15][16] or the SPS apparatus [10,11]. Moreover, a high H cJ surpassing that of the initial HDDR powder by 25% has been obtained with this process.…”
Section: Discussioncontrasting
confidence: 57%
“…Such a phenomenon has not been reported in previous studies using the conventional hot-press [8,[14][15][16] or the SPS apparatus [10,11]. Moreover, a high H cJ surpassing that of the initial HDDR powder by 25% has been obtained with this process.…”
Section: Discussioncontrasting
confidence: 57%
“…Estevez et al (1994) found, for the same composition, some submicron grains with no Nd-rich phase and some isolated by the Nd-rich phase. Ragg et al (1996) analysed the influence of green compacting pressure and hot pressing temperature, time and pressure on the properties of Nd-Fe-B HDDR powder. Magnets with energy products close to 100 kJ m −3 have been achieved for a hot-pressed Nd 14 Fe 79 B 7 magnet.…”
Section: Hot-pressed Methodmentioning
confidence: 99%
“…Further work in Birmingham [49] has focused on the effects of the hot-pressing parameters on the resultant magnetic properties of the hot-pressed fully dense Nd 16 Fe 76 B 8 HDDR magnets. The possibility of reducing the Nd content (and thereby raising the iron content), in order to increase magnetic properties was also investigated.…”
Section: Application and The Scaling Up Of The Hddr Processmentioning
confidence: 99%